SHIAH AND SUNNI CONTESTS IN INDONESIA - M.Husnul Hafiz Rambe; Fahri Azhari; Mailin Mailin (Universitas Dharmawangsa, 2021)
AbstractThis paper arises from the background of a problem that is currently happening in all parts of the world, including in Indonesia, where Shia and Sunni always cause political tensions that stem from the different ideological understandings of these two schools. This is what makes the world's media both offline and online take advantage of the contestation that occurs between Shia and Sunnis with the aim of dividing Muslims in the world. Tensions that occur between Shia and Sunnis greatly affect relations between countries, especially between Arab countries such as Iran and Egypt, even in one country there can be conflicts between Shiites and Sunnis, for example the case of Sampang in Indonesia. The purpose of this paper is to describe what factors influence the conflict between Shia and Sunnis, the extent of the contestation between Shias and Sunnis in terms of politics in the Islamic world and the opinions of religious leaders about Shia and Sunni understanding. Keywords: Shia and Sunni